Analysis of the Financial Performance of National Rural Banks (BPR) before and during Covid-19 pandemic - Riwandari Juniasti (Budapest International Research and Critics University, 2022)
Until now, the condition of the COVID-19 pandemic in Indonesia is still ongoing, this has caused the performance of BPRs to be disrupted. This study aims to analyze whether there are differences in the performance of BPR before the COVID-19 pandemic and during the COVID-19 pandemic at BPR during the period June 2018 to September 2021. BPR's performance is measured by six financial ratios, consisting of the ratio of return to return on assets (ROA), capital adequacy ratio (CAR), non-performing loan ratio (NPL), operating expenses to operating income (BOPO), loan to savings ratio (LDR), and Cash Ratio (CR). This research method uses a quantitative approach with a comparative nature. This type of data collection uses secondary data in the form of BPR financial reports sourced from www.ojk.co.id. The data analysis method used a paid sample-test analysis with the help of the SPSS version 25 program. The results of the study found that (1) there were differences in ROA before the COVID-19 pandemic and during the COVID-19 pandemic. (2) There were differences in CAR before the COVID-19 pandemic and during the COVID-19 pandemic. (3) There was a difference in BOPO before and during the COVID-19 pandemic. (4) There was no difference in NPL before and during the COVID-19 pandemic. (5) There was no difference in LDR before and during the COVID-19 pandemic, and (6) there is no difference in the Cash Ratio (CR) before and during the COVID-19 pandemic.